2017
DOI: 10.1108/jstp-04-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Engagement valence duality and spillover effects in online brand communities

Abstract: Purpose Online brand communities (OBCs) are an effective avenue for brands to engage consumers. While engaging with the brand, consumers simultaneously interact with other OBC members; thus engaging with multiple, interrelated engagement objects concurrently. The purpose of this paper is to explore both positively and negatively valenced consumer engagement with multiple engagement objects, the interplay between these, and the spillover effect from consumers’ engagement with the OBC to their engagement with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
248
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 178 publications
(270 citation statements)
references
References 58 publications
15
248
0
7
Order By: Relevance
“…Despite its influencing power and relationship to key outcomes for firms such as loyalty, lifetime, and shareholder value (Jaakkola and Alexander, 2014;Van Doorn et al, 2010;Verleye, Gemmel and Rangarajan, 2014), the majority of studies address positively valenced CEB; thus largely overlooking the negative side and its ensuing implications (Bowden et al, 2017;Hollebeek and Chen, 2014;McColl-Kennedy et al, 2015).…”
Section: Customer Engagement Behavior (Ceb)mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite its influencing power and relationship to key outcomes for firms such as loyalty, lifetime, and shareholder value (Jaakkola and Alexander, 2014;Van Doorn et al, 2010;Verleye, Gemmel and Rangarajan, 2014), the majority of studies address positively valenced CEB; thus largely overlooking the negative side and its ensuing implications (Bowden et al, 2017;Hollebeek and Chen, 2014;McColl-Kennedy et al, 2015).…”
Section: Customer Engagement Behavior (Ceb)mentioning
confidence: 99%
“…Additionally, apart from a recent study that identified cognitive (subjectivity) and emotional (irritation and community intimacy) triggers of community engagement (Heinonen, 2017), the majority of existing studies on the negative valence of engagement have identified only emotional triggers, such as hatred, anger and stress, towards a service provider, brand or firm (e.g. Bowden et al, 2017;Juric, Smith and Wilks, 2016;Naumann et al, 2017).…”
Section: Influencing Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…more variable) service innovation actor engagement (SIAE) facets. In addition, we distinguish between these actors' positively (vs. negatively) valenced service innovation engagement expressions (Bowden et al, 2017;Hollebeek and Chen, 2014;Alexander et al, 2018), which are synthesized in a conceptual model.…”
Section: Introductionmentioning
confidence: 99%